The impact of shortage implementation of the international regulations on maritime safety - Abuelenin, Ahmed Hany M. (Cogent social sciences, 2017)
This study reveals the most important role of effective marine accident investigation in the improvement of maritime safety through prevention similar casualties from occurring in the future, explores the legal obligations of all parties under different international maritime conventions, and codes. As most of marine accidents resulted from shortage in applying international regulations related to maritime safety, so this research determines, the shortage of application of the international regulations adopted by IMO related to maritime safety, and the shortage of legal measures to support safety at sea and protection or reduce marine pollution. This research also aims to improve special measures for procedures of marine accident investigation, with case study are highlighted, and the importance of identifying the liability. Finally the shortage of civil liability of damage resulting from marine accident under International and National Jurisdiction are discussed with some illustrative cases.